STUDI KASUS TENTANG PROSES PENGAMBILAN KEPUTUSAN MENJADI LESBI - Eka Rizki Meilani; Suwarti Suwarti; Dyah Astorini Wulandari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
The purpose of this study is to examine how the decision-making process becomes lesbian. This research is a qualitative research with case study approach. This research was conducted in Purwokerto Banyumas Regency. Determination of informant in this research using snowball technique method with criterion of informant is lesbian who ever have relationship with same type. Based on these criteria, the researcher get 3 lesbian informants that are M, I and R. Data collecting method by interview and observation. Test data validity by using triangulation method. Data analysis technique used is interactive model consisting of data reduction, data presentation and conclusion.The results of this study describes how the decision making process made a lesbian to be lesbian. The existence of biological factors, psychosocial and psychological on the life of the informant who influential in decision making. Based on the study of the reasons for being lesbian, the responses obtained as data are: for informants M because of the comfortable feel of hanging out with women; informant I is because of hatred of men, because of traumatic experience since childhood witnessed his father's abusive treatment to his mother, so that I appear the feeling of hate toward men, while informant R the reason to be lesbian is because of comfortable pair with woman and physically informant R feel tomboy since childhood. Based on the study collecting information about the life of lesbian hence obtained data that the three informants equally obtain information through lesbian community. Based on the study of how the views of himself and the public about a lesbian? then the data obtained that: Informants M and R admitted that do not care about the opinions of others about lesbi, whereas according to informant I every human being has the right to argue anything about lesbi life. Initially the three informants have no consideration whatsoever to choose to be lesbian and still live lesbiannya life samapai this time. The three informants will remain lesbi and live life with their respective spouses. Keywords: Personal Decision Making Process, Male, Lesbian.